Health Care in Tanzania - Noor Rob (22500160) (2024)
This documentary offers an insightful glimpse into the health infrastructure in Tanzania, taking viewers on a journey through rural villages and a regional hospital. The documentary’s first segment showcases two of the three days of clinical service we provided in Tanzania, which were shot explicitly in Sanya Station and Mtakuja villages. We engaged with doctors, primary school students, and patients, and interviewed some of them about their perspective on the Country’s health system. In the documentary’s second part, we tour Kibosho Hospital. Other Information License: https://creativecommons.org/licenses/by/4.0